VARIASI KONDUKTIVITAS TERMAL PADA PROSES PEMOTONGAN SS400 DENGAN MEDIA PENDINGIN DROMUS TERHADAP KEKASARAN PERMUKAAN - Mastiadi Tamjidillah; Rachmat Subagyo; Rudi Siswanto; Dhonie Adetya Rachman (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Thermal conductivity is a transport phenomenon where the temperature difference causes the transfer of thermal energy from the tip of the blade to the workpiece. The value of thermal conductivity is important for good conductors of surface roughness. Thermal conductivity is influenced by several factors, such as temperature, porosity, and voids. The effect of temperature on thermal conductivity is relatively small, but the conduction increases as the temperature increases, the larger the cavity, the less good the conductivity, which causes low surface roughness. This cutting process pays attention to parameter settings such as temperature, cutting speed, type of knife, and material. Likewise, fluid mechanics and hydraulics parameters such as the velocity of the cooling medium out, the pump pressure, the nozzle cross-sectional area, and the type of cooling medium. The thermal conductivity parameter is set to get the surface roughness results that vary due to thermal changes. Using the Waterjet Cutting Machine for the cutting process of SS400 Steel with a thickness of 12 mm with dromus cooling media to reduce thermal effects and reduce conductivity. With this dromus cooling medium, it is hoped that the surface roughness will be more optimal and avoid overheating. Using the Waterjet Cutting Machine for the cutting process of SS400 Steel with a thickness of 12 mm with dromus cooling media to reduce thermal effects and reduce conductivity. With this dromus cooling medium, it is hoped that the surface roughness will be more optimal and avoid overheating. By varying the temperature between the knife tip and the workpiece, good surface roughness is obtained at variations of the stand off distance of 8, 10, 12 mm, with a dromus at temperatures T1=47, T2=39 and T3=32, fluid velocity 300m/s, and pump pressure. 50.000 psi at turbulent flow Re 4000 gets the optimum result on the surface roughness test, which is 3.47 m.